LUCAS Versus Manual Chest Compression During Ambulance Transport: A Hemodynamic Study in a Porcine Model of Cardiac Arrest. Issue 1 (8th January 2019) - Magliocca, Aurora; Olivari, Davide; De Giorgio, Daria; Zani, Davide; Manfredi, Martina; Boccardo, Antonio; Cucino, Alberto; Sala, Giulia; Babini, Giovanni; Ruggeri, Laura; Novelli, Deborah; Skrifvars, Markus B; et al.
Abstract : Background: Mechanical chest compression (CC) is currently suggested to deliver sustained high‐quality CC in a moving ambulance. This study compared the hemodynamic support provided by a mechanical piston device or manual CC during ambulance transport in a porcine model of cardiopulmonary resuscitation. Methods and Results: In a simulated urban ambulance transport, 16 pigs in cardiac arrest were randomized to 18 minutes of mechanical CC with the LUCAS (n=8) or manual CC (n=8). ECG, arterial and right atrial pressure, together with end‐tidal CO2 and transthoracic impedance curve were continuously recorded. Arterial lactate was assessed during cardiopulmonary resuscitation and after resuscitation. During the initial 3 minutes of cardiopulmonary resuscitation, the ambulance was stationary, while then proceeded along a predefined itinerary. When the ambulance was stationary, CC‐generated hemodynamics were equivalent in the 2 groups. However, during ambulance transport, arterial and coronary perfusion pressure, and end‐tidal CO2 were significantly higher with mechanical CC compared with manual CC (coronary perfusion pressure: 43±4 versus 18±4 mmHg; end‐tidal CO2 : 31±2 versus 19±2 mmHg, P <0.01 at 18 minutes). During cardiopulmonary resuscitation, arterial lactate was lower with mechanical CC compared with manual CC (6.6±0.4 versus 8.2±0.5 mmol/L, P <0.01). During transport, mechanical CC showed greater constancy compared with the manual CC, as represented by a higher CC fraction and a lower transthoracic impedance curve variability ( P <0.01). All animals in the mechanical CC group and 6 (75%) in the manual one were successfully resuscitated. Conclusions: This model adds evidence in favor of the use of mechanical devices to provide ongoing high‐quality CC and tissue perfusion during ambulance transport.